2023
DOI: 10.12968/jowc.2023.32.5.292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplements/intensive nutrition on pressure ulcer healing: a multicentre, randomised controlled study

Abstract: Objective: To investigate the effectiveness of an intensive nutrition intervention or use of wound healing supplements compared with standard nutritional care in pressure ulcer (PU) healing in hospitalised patients. Method: Adult patients with a Stage II or greater PU and predicted length of stay (LOS) of at least seven days were eligible for inclusion in this pragmatic, multicentre, randomised controlled trial (RCT). Patients with a PU were randomised to receive either: standard nutritional care (n=46); inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Pressure injuries are a complex and prevalent healthcare concern, particularly in community settings. Existing nutritional studies on PI wound healing have primarily focused on single-component interventions or hospital-based populations, often lacking individualized dietary support [ 17 , 19 , 20 , 22 ]. Recent trials have explored multi-component interventions but have shown statistically non-significant results [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pressure injuries are a complex and prevalent healthcare concern, particularly in community settings. Existing nutritional studies on PI wound healing have primarily focused on single-component interventions or hospital-based populations, often lacking individualized dietary support [ 17 , 19 , 20 , 22 ]. Recent trials have explored multi-component interventions but have shown statistically non-significant results [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing nutritional studies on PI wound healing have primarily focused on single-component interventions or hospital-based populations, often lacking individualized dietary support [ 17 , 19 , 20 , 22 ]. Recent trials have explored multi-component interventions but have shown statistically non-significant results [ 20 , 22 ]. This study addresses these gaps by implementing a comprehensive PI care bundle intervention, including education, dietetic support with medical nutritional supplements, and trained home care/community nurses in nutrition care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure injuries are a complex and prevalent healthcare concern, particularly in community settings. (19,21) This study addresses these gaps by implementing a comprehensive PI care bundle intervention, including education, dietetic support with medical nutritional supplements, and trained homecare/community nurses in nutrition care. The primary objectives are to evaluate the clinical and cost-effectiveness of the intervention on PI-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Early nutritional studies on PI wound healing generally implements simple (14) single-component interventions using specialized medical nutritional supplements (15)(16)(17)(18), or primarily concentrated on hospitalised patient populations, where the intervention period is inadequate to deliver a positive outcome. (18,19) Recently, a cluster randomised controlled trial (RCT) of 1600 hospitalised patients using a complex multi-component PI prevention intervention (posters/DVD and face-to-face education) showed a statistically non-signi cant reduced hazard ratio for new PI(s) developed. (20,21) However, one of the limitations for this study was the lack of individualised nutritional intervention with supervision.…”
Section: Introductionmentioning
confidence: 99%